Metacryphaeus Tuberculatus and Metacryphaeus australis (Trilobita, Phacopida) from the devonian of the paraná basin: Taxonomy and paleobiogeography - Carbonaro, Fábio Augusto; Meira, Felipe Van Enck; Leme, Juliana De Moraes; Bosetti, Elvio Pinto; Ghilardi, Renato Pirani [UNESP] (Asociacion Paleontologica Argentina, 2016)
Calmoniid trilobites of the genus Metacryphaeus Reed include M. tuberculatus (Kozlowski), M. kegeli Carvalho, Edgecombe and Lieberman, M. meloi Carvalho, Edgecombe and Lieberman, M. rotundatus (Kozlowski), M. giganteus (Ulrich), M. convexus (Ulrich), M. curvigena Lieberman, M. branisai Lieberman, M. caffer (Salter), M. australis (Clarke), and M. allardyceae (Clarke). The geographic distribution of this genus comprises areas of Gondwana, including Bolivia, Peru, Brazil, the Falkland Islands, and South Africa. This study reports a new occurrence of M. tuberculatus in the Paraná Basin (Goiás and Paraná states, Brazil), in both the Alto Garças and the Apucarana sub-basins. Metacryphaeus tuberculatus was compared with all Metacryphaeus species and, especially, with M. australis, which also represents a new record for the Paraná Basin. These new records of M. tuberculatus imply a different dispersion interpretation from that which is known through the literature. Metacryphaeus tuberculatus seems to have originated during the Early Devonian and lived in areas such as Bolivia, Peru, and the Apucarana Sub-basin (Paraná Basin, Brazil). The dispersion between these areas is probably related to the Emsian transgression. During the Givetian, the species presumably migrated towards the Alto Garças Sub-basin (Paraná Basin, Brazil) and the Parnaíba Basin. These facts provide an alternative paleogeographic interpretation to that presented by Tropidoleptus Hall and Exaesiodiscus Moore and Jeffords in Gondwana and suggest a different pattern of migration during the Devonian of Brazil.
Keywords: Alto Gar'as Sub-basin; Apucarana Sub-basin; Brazil; Dispersion